2024
DOI: 10.1001/jamanetworkopen.2023.56098
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Symptoms of Post–COVID-19 Condition and Daily Functioning

Abhishek Jaywant,
Faith M. Gunning,
Lauren E. Oberlin
et al.

Abstract: ImportanceThe frequent occurrence of cognitive symptoms in post–COVID-19 condition has been described, but the nature of these symptoms and their demographic and functional factors are not well characterized in generalizable populations.ObjectiveTo investigate the prevalence of self-reported cognitive symptoms in post–COVID-19 condition, in comparison with individuals with prior acute SARS-CoV-2 infection who did not develop post–COVID-19 condition, and their association with other individual features, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 46 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…In our study, a negative impact on quality of life was also observed at the 6-month follow-up, quantified (EQ-5D-5L) in 22.5% of the 142 patients with mild COVID-19 tested at baseline and at the end of the study. Finally, a survey of 14,767 participants at least 2 months after an acute episode of COVID-19 suggests that cognitive symptoms are common, mostly referred to as mental confusion, associated with worse quality of life [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a negative impact on quality of life was also observed at the 6-month follow-up, quantified (EQ-5D-5L) in 22.5% of the 142 patients with mild COVID-19 tested at baseline and at the end of the study. Finally, a survey of 14,767 participants at least 2 months after an acute episode of COVID-19 suggests that cognitive symptoms are common, mostly referred to as mental confusion, associated with worse quality of life [ 32 ].…”
Section: Discussionmentioning
confidence: 99%